Respuesta :
you need to try and error which you hve to put 0 to replace x or y
3x - 4y = -15
3(0) - 4y = -15
15 = 4y
y = 3.75
or
3x - 4y = -15
3x - 4(0) = -15
3x = -15
x = -5
3x - 4y = -15
3(0) - 4y = -15
15 = 4y
y = 3.75
or
3x - 4y = -15
3x - 4(0) = -15
3x = -15
x = -5
ok so what you do is for this one, eliminate a variable
so we choose to eliminate the y's
multiply first equation by 3 and multiply second equaiton by 4 and add them
9x-12y=-45
16x+12y=220 +
25x+0y=175
25x=175
divide both sides by 25
x=7
sub back
4x+3y=55
4(7)+3y=55
28+3y=55
minus 28 from both sides
3y=27
divide both sides by 3
y=9
x=7
y=9
(x,y)
(7,9)
the solution is (7,9)
so we choose to eliminate the y's
multiply first equation by 3 and multiply second equaiton by 4 and add them
9x-12y=-45
16x+12y=220 +
25x+0y=175
25x=175
divide both sides by 25
x=7
sub back
4x+3y=55
4(7)+3y=55
28+3y=55
minus 28 from both sides
3y=27
divide both sides by 3
y=9
x=7
y=9
(x,y)
(7,9)
the solution is (7,9)